ANALISIS AKUNTANSI PERTANGGUNGJAWABAN PADA HOTEL THE AKMANI LEGIAN - I Gusti Made Agus Rahen Refaya Alvan Putra AJ; I.G.P. Sri Eka Jayanti; I Ketut Puja Wirya Sanjaya (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2025)
Tourism in Bali, particularly at Hotel The Akmani Legian Bali, has seen rapid growth, impacting the accommodation sector significantly. This study analyzes responsibility accounting performance through four centers: cost, revenue, profit, and investment. As Bali's attractiveness as a tourist destination rises, evaluating hotel financial management effectiveness becomes crucial amid increasing competition. The research examines the profitability and adequacy of each responsibility center using methods such as variance analysis, contribution margin, direct profit, controllable profit, Return on Investment (ROI), and Economic Value Added (EVA). Findings reveal that cost and revenue centers yield profitable results, while profit centers show varied outcomes, with some aspects profitable and others not. Investment centers demonstrate positive performance, indicating sound investment decisions. Overall, the responsibility accounting at Hotel The Akmani Legian Bali for 2022-2023 shows satisfactory and profitable outcomes, reflecting efficient resource management. These insights are valuable for hotel management in strategic decision-making aimed at enhancing future financial performance and serve as a reference for hotel operators and stakeholders in developing effective strategies in the hospitality industry